See no evil: Information chains and reciprocity in teams - Eva-Maria Steiger; Roi Zultan (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Transparency in teams can induce cooperation. We study contribution decisions by agents when previous decisions can be observed. We find that an information chain, in which each agent directly observes only the decision of her immediate predecessor, is at least as effective as a fully-transparent protocol in inducing cooperation under increasing returns to scale. In a comparable social dilemma, the information chain leads to high cooperation both when compared to a non-transparent protocol for early movers, and when compared to a fully-transparent protocol for late movers. we conclude that information chains facilitate cooperation by balancing positive and negative reciprocity.
Keywords: C72; C92; D21; J31; M52; 330; team production; public goods; incentives; externality; information; transparency; conditional cooperation; Arbeitsgruppe; Informationsverhalten; Austauschtheorie (Soziologie); Öffentliches Gut; Nichtkooperatives Spiel; Theorie